A gestão do patrimônio arqueológico pelo estado brasileiro: o caso do sítio arqueológico do Morro da Queimada, Ouro Preto-MG - Maria Raquel Alves Ferreira (2011)
The question of environmental conservation is becoming more common in discussions about public management in Brazil. The high concentration of Brazilian population in the urban area causes the crowding of central areas, and the growth of cities towards the suburbs, in most cases, without planning. Another problem is the implementation of infrastructure highly divorced from environmental preservation. Along with the extraction activities carried out without discretion in rural areas, unplanned urban sprawl causes environmental damage, including therein the destruction of existing cultural property in these areas, especially those most vulnerable and fragile, like the nature of archaeological property. In Minas Gerais, the urban historical sites from the colonial era, which were preserved until the mid-twentieth century, resumed their socioeconomic activities since the seventys, with a new economic cycle tied to iron ore and also with the tourist activity, starting a process of urban sprawl, changing the original landscape and deteriorating the existing archaeological heritage around the town. Considering the fact that Historic Urban Sites have specific forms of protection, this study sought to understand how to happen the management of the archeological traces inserted in urban sites declared cultural heritage is done. With this search we tried to learn the concepts and values that guided the preservation of international protocols, the UNESCO legal instruments, and its relationship with national laws and policies for the management of the Brazilian heritage, with a focus on the archaeological heritage. In relation to the field research, we selected the Archaeological site of the Morro da Queimada, located in Ouro Preto-MG, which preserves traces of the former camp miner originated the Historic Urban Site declared national heritage and protected by IPHAN. Through the analysis of the documents from the IPHAN Archive's Administrative, in Ouro Preto, we observed the activity of the Institute for the conservation of the archaeological site in question, its obstacles and achievements. Thus, the research makes a contextualization of the policies to preserve archaeological sites in Brazil and performs a statistical analysis of this process of preservation, especially in the Morro da Queimada. The understanding of this situation is crucial to the achievement of urban policies that fully reconciled development and preservation.